Preparation and activity study of Ruoqiang jujube polysaccharide copper chelate - Moheteer, Aierpati; Li, Jianlong; Abulikemu, Xireli; Lakho, Shakeel Ahmed; Meng, Yan; Zhang, Jiayi; Khand, Faiz Muhammad; Leghari, Ambreen; Abula, Saifuding; Guo, Qingyong; Liu, Dandan; Mai, Zhanhai; et al. (Frontiers in Pharmacology, 2024)
Background: Polysaccharide metal chelate exhibit both immunoregulatory activity and metal element supplementation effects. Methods: In this study, Ruoqiang jujube polysaccharide copper chelate (RJP-Cu) was prepared and the preparation conditions were optimized using the response surface method. Subsequently, RJP-Cu was administered to lambs to evaluate its impact on growth performance, copper ion (Cu2+) supplementation, immune enhancement, and intestinal flora was evaluated. Results: The results indicated that optimal RJP-Cu chelation conditions included a sodium citrate content of 0.5 g, a reaction temperature of 50°C, and a solution pH of 8.0, resulting in a Cu2+ concentration of 583°mg/kg in RJP-Cu. Scanning electron microscopy (SEM) revealed significant structural changes in RJP before and after chelation. RJP-Cu displaying characteristic peaks of both polysaccharides and Cu2+ chelates. Blood routine indexes showed no significant differences among the RJP-Cu-High dose group (RJP-Cu-H), RJP-Cu-Medium dose group (RJP-Cu-M), RJP-Cu-low dose group (RJP-Cu-L) and the control group (p > 0.05). However, compared with the control group, the RJP-Cu-H, M, and L dose groups significantly enhanced lamb production performance (p < 0.05). Furthermore, RJP-Cu-H, M, and L dose groups significantly increased serum Cu2+ concentration, total antioxidant capacity (T-AOC), catalase (CAT), and total superoxide dismutase (T-SOD) contents compared with control group (p < 0.05). The RJP-Cu-H group exhibited significant increases in serum IgA and IgG antibodies, as well as the secretion of cytokines IL-2, IL-4, and TNF-α compared to the control group (p < 0.05). Furthermore, RJP-Cu-H group increased the species abundance of lamb intestinal microbiota, abundance and quantity of beneficial bacteria, and decrease the abundance and quantity of harmful bacteria. The RJP-Cu-H led to the promotion of the synthesis of various Short Chain Fatty Acids (SCFAs), improvements in atrazine degradation and clavulanic acid biosynthesis in lambs, while reducing cell apoptosis and lipopolysaccharide biosynthesis. Conclusion: Thus, these findings demonstrate that RJP-Cu, as a metal chelate, could effectively promote lamb growth performance, increase Cu2+ content, and potentially induce positive immunomodulatory effects by regulating antioxidant enzymes, antibodies, cytokines, intestinal flora, and related metabolic pathways.